La discriminación que se hace a los aprendices y operarios, al excluirlos de los beneficios remunerativos establecidos en el Código de trabajo - Yanez Apolo, Gladys Beatriz (2016)
The Labour Code determines all remunerative benefits that a worker must receive for their work, the main we have the right to fair remuneration, the payment of the thirteenth and fourth remuneration, reserve funds and payment of utilities. The Labour Code in relation to the workers and apprentices literally states "Art. 101, "Exemption from utilidades.- remain exempt from the profit sharing artisans about their workers and apprentices. Also our 115 Labor Code in its article states: Exclusion of operators and aprendices.- are excluded from bonuses to which this paragraph relates, operators of craftsmen and apprentices. Analyzed the laws invoked before the Labour Code, to easily view we can realize that what will discriminate against the most fundamental rights of workers. These rules make apprentices and workers who perform work equal to or greater than other workers, can not receive the same benefits such as payment of the thirteenth and fourth remuneration, payment of profits and reserve funds. This leads to a serious violation of their rights fully established in the Constitution, as it is entitled to formal equal, ie that all are equal before the law and therefore must be treated in the same way without discrimination of any kind; situation that is not fulfilled in the case of apprentices or workers.